Digital Comics as an Innovative Strategy to Foster Reading Interest among Fifth-Grade Students: Evidence from Indonesian Elementary Education - Mu'awiah Mu'awiah; Dina Khairiah; Muhammad Amien Rais (Yayasan Zia Salsabila, 2025)
Numerous studies have documented low reading interest among Indonesian elementary students, yet empirical exploration of innovative digital media interventions remains limited, particularly in rural contexts. This study aims to analyze the effectiveness of digital comic media in enhancing fifth-grade students' reading interest. Classroom action research with cyclical design was conducted at SD Negeri 122 Sayur Maincat, Mandailing Natal Regency, involving 29 participants. Data were collected through learning activity observations and reading interest questionnaires, analyzed quantitatively-descriptively. Results revealed significant improvement in reading interest from baseline 27.5% (low category) to 86.2% (very high category) at Cycle II completion. Teachers' instructional management capacity increased from 75% to 82.5%, while student engagement rose from 77% to 85%. This study confirms that integrating digital comics as innovative pedagogical strategy effectively transforms students' literacy engagement in resource-constrained settings. The findings suggest teachers can adopt visual-digital media to address low reading motivation, contributing to quality literacy achievement aligned with SDG 4.